2015
DOI: 10.1186/s12979-015-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins and hormesis in the diagnosis and treatment of neurodegenerative diseases

Abstract: Modulation of endogenous cellular defense mechanisms via the vitagene system represents an innovative approach to therapeutic intervention in diseases causing chronic tissue damage, such as in neurodegeneration. The possibility of high-throughoutput screening using proteomic techniques, particularly redox proteomics, provide more comprehensive overview of the interaction of proteins, as well as the interplay among processes involved in neuroprotection. Here by introducing the hormetic dose response concept, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 218 publications
1
91
0
Order By: Relevance
“…Overall, altered proteostasis, including imbalance in protein synthesis, folding (e.g., altered heat shock proteins), and degradation, may represent a key initiating mechanism underlying “normal” aging changes at OFC. This is particularly important in light of an emerging concept that altered proteostasis could lead to age-related neurodegenerative disorders (Dattilo et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Overall, altered proteostasis, including imbalance in protein synthesis, folding (e.g., altered heat shock proteins), and degradation, may represent a key initiating mechanism underlying “normal” aging changes at OFC. This is particularly important in light of an emerging concept that altered proteostasis could lead to age-related neurodegenerative disorders (Dattilo et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Signaling by ROS, produced during aerobic metabolism, follows the mechanistic determinism of hormetic laws, whereby at low levels free radical generation regulates a wide array of physiological responses, whereas at high levels, such as in abnormal cell metabolism conditions, cell function and viability are under threat (Calabrese V et al, ). Thus, an increase in ROS formation with the associated disruption of redox homeostasis results in dysfunction of biologically relevant mechanisms involved in neuronal plasticity (Calabrese V et al, ; Dattilo et al, ). As a basic principle of a hormetic phenomenon, restoration of disrupted homeostasis can induce adaptive conditions associated with higher levels of stress tolerance than the prior stage.…”
Section: Nlrp3: Structure Activation and Regulationmentioning
confidence: 99%
“…Despite the current interest in hormesis by the toxicology community, quantitatively similar hormetic U‐shaped dose responses have long been recognized by researchers to be involved with factors affecting memory, learning, and performance, as well as nutritional antioxidants and oxidative stress–mediated neurodegenerative responses in cellular models for various diseases such as AD and PD (Calabrese EJ, ). Several lines of in vitro evidence have implicated ROS in the pathogenesis of neuronal death (Calabrese V et al, 2010), and different markers of oxidative stress are found in postmortem examination of brains from patients with many neurodegenerative disorders (Dattilo et al, ). DNA oxidation, protein oxidation, and lipid peroxidation have been reported in brain regions containing NFTs and senile plaques from patients with AD (Calabrese V et al, ).…”
Section: Nlrp3: Structure Activation and Regulationmentioning
confidence: 99%
“…Brain inflammation has been linked to many of these diseases, including amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), Parkinson's disease (PD) and, particularly, Alzheimer's disease (AD) 5 . To adapt to environmental changes and survive different types of injuries, brain cells have evolved networks of responses that detect and control diverse forms of stress 6,7 . Consistent with this notion, integrated survival responses exist in the brain, which are under control of redox-dependent genes, called vitagenes (Figure 1), including heat shock proteins (Hsps), sirtuins, thioredoxin and lipoxin A4.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, integrated survival responses exist in the brain, which are under control of redox-dependent genes, called vitagenes (Figure 1), including heat shock proteins (Hsps), sirtuins, thioredoxin and lipoxin A4. These proteins actively operate in detecting and controlling diverse forms of stress and neuronal injuries [7][8][9] . LXA4, a metabolic product of arachidonic acid, is considered an endogenous ''stop signal'' for inflammation, and shows potent anti-inflammatory properties in many inflammatory disorders, such as nephritis, periodontitis, arthritis, inflammatory bowel disease 10 .…”
Section: Introductionmentioning
confidence: 99%